Unravelling chironomid biodiversity response to climate change in subarctic lakes across temporal and spatial scales - Belle, Simon (2022)
We combined paleolimnological reconstructions and space-for-time substitutions to unravel chironomid biodiversity responses to climate change in subarctic mountains across temporal and spatial scales. Using sediment records, we found that long-term temporal changes in chironomid taxonomic diversity were mainly induced by the temperature tolerance/optimum of species, while little changes in functional diversity were found due to the replacement of similar functional-type taxa within the community. Overall, paleolimnological reconstructions suggested the selection of larger chironomid species by long-term climate cooling and little changes in trophic guilds. Space-for-time substitutions showed, however that low-elevation lakes with forested have more sediment-feeding taxa and larger larvae than high-elevation lakes, thus, suggesting the selection of large chironomid morphotypes with a sediment-feeding mode under warmer climate. Space-for-time substitutions and paleolimnological reconstructions, therefore, gave contrasting results for the link between climate and functional diversity of chironomid communities, likely because space-for-time substitutions failed to match the extent of both spatial and temporal climatic gradients. We suggest that future studies must address biodiversity issues across both temporal and spatial scales as an improved understanding of biodiversity responses to climate change may help us to understand how biodiversity will be affected by ongoing and future change.